Taguchi Parametric Optimization of Theobroma Cocoa-Derived Magnetite Nanoparticles: Synthesis, Pegylation, and Magnetic Hyperthermia Potential - Mohamed Abdelsamea; O. M. Lemine; Emma Ziezie Ziezie; Mohd Tarmizi; Norazalina Saad; Huey Fang Teh; Ahmad Kamil Mohd Jaaffar; Mohamed Ahmed Ibrahim; Che Azurahanim Che Abdullah (Journal of Water and Environmental Nanotechnology)
Magnetite nanoparticles (MNPs) have shown excellent heating responses under magnetic excitation, making them ideal for hyperthermia applications. Using cocoa bean shell (CBS) extract as a bio-reducing and stabilizing agent, we implemented the Taguchi optimization method with an L9 orthogonal array. The optimization focused on the particle size of MNPs and Pegylated-MNPs, which was measured using the dynamic light scattering (DLS) technique. Taguchi analysis revealed that pH is the most influential factor on the size of MNPs in green synthesis while stirring speed is the most significant factor for the size of Pegylated-MNPs during the Pegylation process. Furthermore, the optimized nanoparticles were analyzed using ZP, FT-IR, FE-SEM, and EDX analysis. The ideal sizes of MNPs and Pegylated-MNPs measured using DLS were 115 nm and 69 nm, respectively. Remarkably, at a concentration of 5 mg/mL, MNPs, and Pegylated-MNPs quickly dissipated heat, achieving maximum intrinsic loss powers (ILP) of 1.29 nHm²/kg and 0.694 nHm²/kg and specific absorption rates (SAR) of 135.17 W/g and 60.18 W/g. Hyperthermia temperatures were reached within approximately 7 and 10 minutes, with maximum temperatures of 50°C and 46°C. Our results strongly advocate for the potential of optimized biosynthesized MNPs and Pegylated-MNPs as highly effective options for magnetically triggered biomedical hyperthermia applications.